Evidence for Ancient Origins of Bowman-Birk Inhibitors from Selaginella moellendorffii. Issue 3 (14th March 2017) - James, Amy M.; Jayasena, Achala S.; Zhang, Jingjing; Berkowitz, Oliver; Secco, David; Knott, Gavin J.; Whelan, James; Bond, Charles S.; Mylne, Joshua S.
Abstract : A sequence from spikemoss uncovers the true extent of the Bowman-Birk Inhibitor family to be wider than cereals and legumes, solving a long-standing mystery about their origins. Abstract: Bowman-Birk Inhibitors (BBIs) are a well-known family of plant protease inhibitors first described 70 years ago. BBIs are known only in the legume (Fabaceae) and cereal (Poaceae) families, but peptides that mimic their trypsin-inhibitory loops exist in sunflowers ( Helianthus annuus ) and frogs. The disparate biosynthetic origins and distant phylogenetic distribution implies these loops evolved independently, but their structural similarity suggests a common ancestor. Targeted bioinformatic searches for the BBI inhibitory loop discovered highly divergent BBI -like sequences in the seedless, vascular spikemoss Selaginella moellendorffii . Using de novo transcriptomics, we confirmed expression of five transcripts in S. moellendorffii whose encoded proteins share homology with BBI inhibitory loops. The most highly expressed, BBI3, encodes a protein that inhibits trypsin. We needed to mutate two lysine residues to abolish trypsin inhibition, suggesting BBI3's mechanism of double-headed inhibition is shared with BBIs from angiosperms. As Selaginella belongs to the lycopod plant lineage, which diverged ∼200 to 230 million years before the common ancestor of angiosperms, its BBI -like proteins imply there was a common ancestor for legume and cereal BBIs. Indeed, we discovered BBI sequences in six angiosperm families outside the Fabaceae and Poaceae. These findings provide the evolutionary missing links between the well-known legume and cereal BBI gene families.